The Use of Total Physical Response for Teaching English Vocabulary at SMPN 1 Kramatwatu - Wahyuni, A'i; Maulana, Apriza Rizky; Nupus, Neng Ana Aprilya; Rahmawati, Ratu Ayu; Sintawati, Fairus (JEDLISH : Journal Of Education and English Language Teaching, 2023)
This study discusses the application of the TPR method at SMPN 1 KRAMATWATU for grade 8F students. This study takes how effective the method is. The result shows that students understand more when using the TPR method. Researchers used descriptive qualitative when conducting the research.